Congenital glucose-galactose malabsorption due to SLC5A1 mutation: a case of hypernatraemic dehydration - Hanife Aysegul Arsoy,; Hatice Zeynep Terzi,; Arzu Oto,; Murat Tutanc, (Journal of the Pakistan Medical Association, 2026)
Congenital glucose-galactose malabsorption (GGM) is an exceedingly uncommon autosomal recessive metabolic state defined by persistent diarrhoea along with serious dehydration. It is a disease that is difficult to consider in differential diagnosis and may be fatal if left untreated. This report details the clinical and diagnostic progress of a two-month-old Turkish infant exhibiting episodes of severe recurrent watery diarrhoea. Molecular testing revealed that the patient has a compound heterozygous variant in SLC5A1. The patient has been asymptomatic with fructose-based formula. Paediatricians should take into account unexpected congenital causes while looking for common causes in infants who present with chronic diarrhoea, particularly when accompanied by hypernatraemic dehydration. Early diagnosis and swift treatment is important in order to avoid major complications from undetected GGM. Genetic testing is highly encouraged as it helps in early identification of these patients, preventing major complications, and improving clinical outcomes. Keywords: Diarrhoea, SLC5A1, Glucose-galactose malabsorption.